Simultaneous Liver Kidney Transplant in Elderly Patients With Chronic Kidney Disease: Is There an Appropriate Upper Age Cutoff?. Issue 12 (December 2020) - Goldberg, David S.; Vianna, Rodrigo M.; Martin, Eric Fleming; Martin, Paul; Arosemena Benitez, Leopoldo Ramon; O'Brien, Christopher Blackburn; Bhamidimarri, Kalyan R.
Abstract : Background: The aging of liver transplant (LT) recipients, the weighting of the model for end-stage liver disease score, and the increased prevalence of nonalcoholic steatohepatitis has led to an increased number of older LT recipients with pre-LT chronic kidney disease (CKD). There are limited data on the impact of increased recipient age on post-simultaneous liver-kidney (SLK) transplant outcomes among patients with CKD, leading some centers to employ subjective age cutoffs for potential SLK recipients. Methods: We evaluated United Network for Organ Sharing data of adult SLK recipients from February 27, 2002, to December 31, 2018, restricted to recipients with ≥90 days of waiting time and CKD (estimated glomerular filtration rate persistently <60 mL/min/1.73 m2 for ≥90 d using the modification of diet in renal disease-4 equation). We fit mixed-effects Cox regression models (center as random effect) to evaluate the association of recipient age and patient survival. Results: Among 3146 SLK recipients with CKD, nearly two-thirds were 50–64 years of age, while 465 (14.8%) and 93 (3.0%) were 65–69 years and ≥70 years, respectively. Compared with nondiabetic SLK recipients aged 50–59 years, SLK recipients ≥70 years of age without diabetes (hazard ratio, 1.97; 95% CI, 1.20-3.23; P = 0.007) and with diabetes (hazard ratio, 1.90; 95% CI, 1.16-3.09; P = 0.01) had higher mortality compared with the reference group. In absolute terms, SLK recipients ≥70 years of age had 25% lower patient survival at 5 years compared to recipients aged 40–49 years. Conclusions: Although careful selection is required of any SLK recipient, especially those with increased comorbidities, there are no objective data to justify a specific age cutoff <70 years among potential SLK recipients with CKD.